Gamma glutamyl transferase and its fractions to predict coronary artery calcium and outcome in the general population. (14th October 2021) - Chiappino, S; Aimo, A; Musetti, V; Masotti, S; Paolicchi, A; Franzini, M; Della Latta, D; Ripoli, A; Martini, N; Susini, C; Piagneri, V; Storti, S; et al.
Abstract: Background: Gamma glutamyl transferase (GGT) is a risk factor for plaque destabilization, particularly its fraction with the highest molecular weight (big-GGT, b-GGT). We explored the interplay between GGT, computed tomography (CT) findings that predict cardiovascular risk (coronary artery calcium [CAC] and epicardial fat volume [EFV]), and 10-year outcome. Methods: Between May 2010 and October 2011, subjects aged between 45 and 75 years living in a city of Tuscany (Italy) and free from known cardiovascular disease were invited to participate to a screening including a CT scan. Results: A subgroup of study participants (n=898, 65%) had total GGT and GGT fractions quantified (median age 65 years [25th-75th percentile: 55–70 yrs], 46% males, median 10-year risk of myocardial infarction or death based on the Framingham score 6% [2–11%]). GGT predicted CAC (Exp(B) 0.099, p=0.002) and EFV (Exp(B) 0.102, p=0.003) in a model including age, gender, diabetes, current or previous smoking status, low-density lipoprotein cholesterol, high-sensitivity C-reactive protein, and aspirin therapy. Over 10.3 years (9.6–10.8), 74 individuals died (8%), and 36 (4%) experienced the composite of cardiovascular death or coronary revascularization. The risk of all-cause death and the composite endpoint increased quite steeply with GGT values, with thresholds of 19 UI and 20 IU, respectively (Figure). GGT predicted both endpoints independently from the Framingham 10-year risk (hazard ratio [HR] 1.01, 95% CI 1.01–1.02, p=0.004, and HR 1.01, 95% CI 1.01–1.02, p=0.002, respectively), as well as a model including CT findings. bGGT had the highest area under the curve value to predict the composite endpoint (0.586). Conclusions: In a general population setting, plasma GGT independently predicts CAC and EFV, and the risk of all-cause death or a composite cardiovascular endpoint. Funding Acknowledgement: Type of funding sources: None.